Answer:
6 and -4
Step-by-step explanation:
a + b = 2
a - b = 10
Solve:
from the first eq.
a = 2 - b
replacing this value in the second eq.
(2-b) - b = 10
2 - 2b = 10
-2b = 10 - 2
-2b = 8
b = 8/-2
b = -4
from the second eq.
a - b = 10
a - (-4) = 10
a + 4 = 10
a = 10 - 4
a = 6
Check:
from the first eq.
6 + (-4) = 2
6 - 4 = 2
Answer:
x = 71°
Step-by-step explanation:
because the triangle shown in the image is an isosceles if the top angle is 38 the sum of other two angles must be 142 which is ,if divided by 2, makes 71
Step-by-step explanation:
3x+x=-7-5
4x=-12
x=-12/4
x=-3
Answer:
220
Step-by-step explanation:
<u>first we have by Bracket of BODMAS rule then we have to multiply 10 *8 = 80</u>
<u>first we have by Bracket of BODMAS rule then we have to multiply 10 *8 = 80then we have to open bracket 80 +150</u>
<u>first we have by Bracket of BODMAS rule then we have to multiply 10 *8 = 80then we have to open bracket 80 +150 = 220</u>
<u> (10*8) +15</u>
<u>Solution</u>
<u>Solution= (80) +150</u>
<u>Solution= (80) +150= 80+150</u>
<u>Solution= (80) +150= 80+150=. 220</u>
<u>Solution= (80) +150= 80+150=. 220 </u>